2010
DOI: 10.1055/s-0030-1252016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peripheral Kisspeptin Administration on Adiponectin, Leptin, and Resistin Secretion Under Fed and Fasting Conditions in the Adult Male Rhesus Monkey (Macaca mulatta)

Abstract: In the last few years, kisspeptin-KISS1R signaling has appeared as a major regulator of the reproductive function in several vertebrate species. However, KISS1(encoding kisspeptin) and its putative receptor, KISS1R, are expressed in several other tissues. Adipose tissue, which secretes many peptides with diverse functions in normal physiology, expresses KISS1, which is modulated by gonadal steroids as well as by body nutritional status. Similarly, KISS1Rexpression is also found in adipose tissue, but the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…Our previous study indicated that the kisspeptin significantly increased plasma adiponectin levels in the adult male rhesus monkey (Wahab et al, 2010). This was a novel finding and suggested that kisspeptin acted peripherally on adipose tissues and stimulated adiponectin release.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Our previous study indicated that the kisspeptin significantly increased plasma adiponectin levels in the adult male rhesus monkey (Wahab et al, 2010). This was a novel finding and suggested that kisspeptin acted peripherally on adipose tissues and stimulated adiponectin release.…”
Section: Discussionmentioning
confidence: 85%
“…Blood samples were collected at 15-min intervals for 60 min before P234/ vehicle administration and until 210 min after the KP-10 administration. As mentioned above, the doses of P234 and KP-10 were calculated based on previous work in adult female (Roseweir et al, 2009) and adult male (Wahab et al, 2010) rhesus monkeys, respectively. 2.5.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations